KEGIATAN BELAJAR PARTISIPATIF - Sariah Sariah (An-Nida', 2012)
Participative learning activity constitute source effort studies for mengikut to attach studying citizen in learning activity or with other meaning goes along it citizen studies kedala learning program that is rendered in three steps which is program plannings, performing and evaluation activity. Activity process studies participative potbound of tradition already grow at society since preceding epoch, this learned activity potbound of social point and religion norm already well-established deep society life as mutually togetherness, mutually utilizes and interdependence. In participative learning performing ranges six steps which is familiarity constructions, the need formulation identification aim studies, collation programs performing studying activity activity study, estimation to program and result and activity impact studies.